2021
DOI: 10.3389/fmed.2021.772413
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Activity in Patients With Extracorporeal Membrane Oxygenation Life Support: An Observational Pilot Study

Abstract: Background: Extracorporeal membrane oxygenation (ECMO) life support has become an integral part of intensive care. The endotoxin activity assay (EAA) is a useful test to measure endotoxemia severity in whole blood. To date, no information is available regarding the EAA levels and their effect on clinical outcomes in critically ill patients with ECMO support.Methods: This prospective observational pilot study enrolled adult critically ill patients with ECMO support from August 2019 to December 2020. The EAA lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The fourth study reported endotoxin activity in 39 patients under venoarterial extracorporeal membrane oxygenation (VA-ECMO). In these patients (16 cardiac arrest, 17 heart failure, 4 post cardiotomy and 2 septic shock), the incidence of endotoxemia was only 9% within the first 24 h and 5% between 24 and 48 h. There was no difference in endotoxin activity between survivors and non-survivors [ 54 ].…”
Section: The Evidence: Clinical Findingsmentioning
confidence: 99%
“…The fourth study reported endotoxin activity in 39 patients under venoarterial extracorporeal membrane oxygenation (VA-ECMO). In these patients (16 cardiac arrest, 17 heart failure, 4 post cardiotomy and 2 septic shock), the incidence of endotoxemia was only 9% within the first 24 h and 5% between 24 and 48 h. There was no difference in endotoxin activity between survivors and non-survivors [ 54 ].…”
Section: The Evidence: Clinical Findingsmentioning
confidence: 99%
“…Endotoxemia reduces cardiac performance [57] and can propagate a low cardiac output state [58]. Despite sound rationale, three small studies [59][60][61] have failed to identify direct proof of endotoxemia in patients with CS with the caveat that no study has hitherto reported quantitative measurement (i.e. mass) of circulating endotoxins and many endotoxin assays have inherent detection limitations.…”
Section: The 'Host Response' To Cardiogenic Shockmentioning
confidence: 99%